Tratamento tardio de luxação extrusiva por meio de reimplante intencional - Santos, Eluma Alves dos [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Some dental trauma situations may require different techniques employed in the routine professional. Knowing the repair process in these cases is of great importance for the correct indication. The aim of this study was to report a case of extrusive dislocation treated by intentional replantation. The Y.F. patient, 16 years old, female, attended the Integrated Clinic Araçatuba Dental School for treatment of trauma in maxillary anterior teeth, six days after the incident. On examination it was found that the elements 21 and 22 had to extruded 4 mm from the side, and heightened mobility and pain to percussion. Radiographically, there was an increase of the periodontal ligament space mainly in the periapical region. As the manual repositioning was not opted for the intentional reimplantation followed endodontic treatment of 21 and 22. It carried out the extraction of the teeth, followed by curettage and thorough irrigation with saline for removal of the clot, followed by reimplantation of the tooth. A containment with orthodontic wire was maintained for 14 days, when it started endodontic treatment. Calcium hydroxide dressing changes were performed every two weeks and for 30 days following the final filling. The patient was followed up for 13 months where we observed the aesthetic and functional rehabilitation of the teeth. It was concluded that the knowledge and multidisciplinary approaches are essential for the treatment of cases of trauma dentoalveolar . Intentional reimplantation allowed a conservative approach for the case of late treatment extrusive dislocation, resulting in a clinical success with no reabsorption by the observed period

Algumas situações de traumatismo dentário podem requerer técnicas diferentes das empregadas na rotina do profissional. Conhecer o processo de reparo nesses casos se torna de grande importância para a sua correta indicação. O objetivo do presente trabalho foi relatar um caso clínico de luxação extrusiva tratada por reimplante intencional. O paciente Y.F., 16 anos de idade, gênero feminino, compareceu à Clínica Integrada da Faculdade de Odontologia de Araçatuba para tratamento de traumatismo nos dentes ântero-superiores, 6 dias após o ocorrido. No exame clínico constatou-se que os elementos 21 e 22 apresentavam-se extruídos 4 mm em relação ao contralateral, além de mobilidade acentuada e dor à percussão. Radiograficamente, observou-se aumento do espaço do ligamento periodontal principalmente na região periapical. Como o repocionamento manual não foi possível optou-se pelo reimplante intencional. Realizou-se a extração dos dentes, seguido de curetagem e irrigação cuidadosa com soro fisiológico para remoção do coágulo, seguido do reimplante dentário. Uma contenção com fio ortodôntico foi mantida por 14 dias, quando então se iniciou o tratamento endodôntico. Trocas de curativo de hidróxido de cálcio foram realizadas quinzenalmente por 30 dias e em sequência a obturação definitiva. O paciente foi acompanhado por 13 meses onde foi observada a reabilitação estética e funcional dos dentes
Keywords: Extrusão ortodôntica; Reimplante dentário; Reabsorção da raiz; Tooth Replantation